Corporate governance in Malaysia: A glass half full? - Ng, Sin Huei; Yeoh, Ken Kyid (Institute of Public Enterprise, 2012)
It is believed that extensive political involvement in business fundamentally impacts the overall quality of both firm- and country-level corporate governance in a particular country. Using the corporate and institutional environment in Malaysia as our chosen example, we aim to show the profound influence that national government policies and approaches to the running of their respective capital markets has on the corporate governance practices and norms in a particular country.